Memetic images and the use and representation of the past: The US war of independence and Donald Trump’s presidency - Venegas Ramos, Alberto (Hispania Nova, 2021)
The goal of this paper is to study the forms and uses of the past in digitally-created images that are reproduced in virtual spaces using as an example the famous painting Washington crossing the Delaware (1851) by Emanual Leutze and the subsequent changes and adaptations of this work of art. Based on the latest studies of visual culture, cultural memory and previous literature on the subject matter, we will analyse a case study: digital and virtual images created around Donald Trump’s presidency and the memories of the country’s war of independence. This paper will aim to define the ways in which new media relate to and use the past as well as to consider those formats as valid sources for understanding the past, as well as active spaces of discussion and debate about past times and their use in the present.